2018
DOI: 10.1002/mbo3.786
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the gut microbiota of hornbill and toucan in captivity

Abstract: Gut microbiota plays an important role in animals and are considered microbial organs. Hornbill and toucan are birds of the same ecotypes with high appreciative value. In this study, we characterized and compared the gut microbiota of toco toucan ( Ramphastos toco ), great hornbill ( Buceros bicornis ) and wreathed hornbill ( Rhyticeros undulatus ) using 16S rRNA high‐throughput sequencing technology, and further discussed the influence of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
10
1
Order By: Relevance
“…Functionally, Actinobacteria was regard to participate in the decomposition of organic matter in soil and sediments, and studies in mammals have shown a positive correlation with fiber intake (Henning et al 2017). While some carp species (Li et al 2018b), birds (Sun et al 2018) and mammals (Gu et al 2013;Andersson et al 2008) shared Bacteroidetes as the most common phylum (relative abundance > 10%), Firmicutes (mostly the genus of Tyzzerella 3 in this work) was found with relative abundance evenly distributed among the detected samples.…”
Section: Discussionsupporting
confidence: 52%
“…Functionally, Actinobacteria was regard to participate in the decomposition of organic matter in soil and sediments, and studies in mammals have shown a positive correlation with fiber intake (Henning et al 2017). While some carp species (Li et al 2018b), birds (Sun et al 2018) and mammals (Gu et al 2013;Andersson et al 2008) shared Bacteroidetes as the most common phylum (relative abundance > 10%), Firmicutes (mostly the genus of Tyzzerella 3 in this work) was found with relative abundance evenly distributed among the detected samples.…”
Section: Discussionsupporting
confidence: 52%
“…The taxonomic composition of blue tit fecal bacterial microbiota was dominated by Actinobacteria, Proteobacteria, and Firmicutes. Proteobacteria and Firmicutes have been previously reported to dominate bird fecal microbiota [68][69][70]. Interestingly, we found that Actinobacteria were very abundant in bird feces, but this group was not typically dominant in bird fecal microbiota in other studies.…”
Section: Discussioncontrasting
confidence: 49%
“…OTUs accounting for less than 0.001% of total sequences across all samples were discarded. To minimize the difference of sequencing depths across samples, an average, rounded rarefied OTU table was generated by averaging 100 evenly resampled OTU subsets under the 90% of the minimum sequencing depth for further analysis (Liu et al, 2019; Sun et al, 2019).…”
Section: Methodsmentioning
confidence: 99%